X-ray photoelectron spectroscopy of nanopowders of ZrO₂-Y₂O₃-Cr₂O₃ compounds - Korduban, A.M.; Yashchishyn, I.A.; Konstantinova, T.E.; Danilenko, I.A.; Volkova, G.K.; Glazunova, V.A. (Functional Materials, 2007)
The X-ray photoelectron spectroscopy investigation of doped zirconium dioxide nanopowders of ZrO₂ + 3 mol.% Y₂O₃ + 0.5 % Cr₂03, ZrO₂ + 0.5% Cr₂O₃ and ZrO₂ + 3 mol.% Y₂O₃ compositions has been carried out in order to obtain information about surface states of the nanoparticles. Samples of all compositions are nonstoichiometric and include four states of zirconium atoms: Zr⁴⁺(O²⁻, Zr⁴⁺(OH), Zr³⁺, and Zr²⁺. Although initial states of samples doped with yttrium and chromium and with yttrium only differ slightly from one another, after calcination at 600 °C in air for 1 h, intensity of component corresponding to Zr-OH bond in case of Y-doping decreased by 58% and in case of Y and Cr doping by 27% only. This fact shows that doping with chromium oxide slows down depiction of OH groups and explains nanopowders crystallization process delay.